Variability in management of early severe sepsis. Issue 2 (15th February 2010) - Reade, Michael C; Huang, David T; Bell, Derek; Coats, Timothy J; Cross, Anthony M; Moran, John L; Peake, Sandra L; Singer, Mervyn; Yealy, Donald M; Angus, Derek C; ,
Abstract : Objective: A study was undertaken to characterise how doctors in emergency medicine (EM), acute medicine (AM) and critical care (ICU) in the UK, USA and Australia and New Zealand (ANZ) approach the initial resuscitative care of patients with severe sepsis. Methods: In 2007, members on the mailing lists of UK, US and ANZ EM, ICU and AM specialist organisations were invited to answer an anonymous scenario-based online survey. Respondents described their management of a patient with pneumonia and signs of sepsis. Multiple-choice questions were based on the Surviving Sepsis Campaign (SSC) 6-hour resuscitation bundle guidelines while avoiding the specific terms "sepsis" and "SSC guidelines". Results: The response rate was 21% (2461/11 795). Only two respondents (0.1%) complied with all SSC resuscitation recommendations. Inter-specialty and inter-country variations included differences in reporting initial lactate measurement (ranging from 30% in US-EM to 79% in UK-EM), fluid resuscitation targeting a central venous pressure of 8–12 mm Hg (from 15% in ANZ-ICU to 60% in UK-EM), blood transfusion for a central venous oxygen saturation <70% and haematocrit <30% (from 15% in ANZ-ICU to 70% in US-EM and UK-EM) and insertion of invasive monitoring (intra-arterial catheter: 89% in UK-ICU vs 20% in US-EM; central venous catheter: 83% in UK-ICU vs 44% in US-EM). 81% of respondents identified at least one reason why they did not implement all the recommendations; the reasons varied by region and specialty. Conclusions: Reported management of early sepsis varies between specialities and countries, and the responses do not follow SSC guidelines. Concerns relate to knowledge, attitudes and resources.